PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI, DANA UMUM, ALOKASI KHUSUS DAN BAGI HASIL TERHADAP KINERJA KEUANGAN PEMERINTAH EKS KARESIDENAN SURAKARTA TAHUN ANGGARAN 2016-2023 - Candra Ismayasari; Yuwita Ariessa; Wikan Budi (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of local revenue, general allocation funds, special allocation funds and profit sharing funds on government financial performance. The population of this study observed the financial reports for the realization of the APBD for the former Surkarta Residency via the website www.djpk.kemenkeu.go.id for the 2016-2023 fiscal year. Based on the observations made, it was found that the regional original income variable did not have a significant effect on the financial performance of the former Surakarta residency government in 2016-2023. The general allocation fund variable has a significant negative effect on the financial performance of the former Surakarta residency government in 2016-2023. The special allocation fund variable does not have a significant effect on the financial performance of the former Surakarta residency government in 2016-2023. The profit sharing variable does not have a significant effect on the financial performance of the former Surakarta Residency government in 2016-2023.